Social Justice in HCI: Current Streams, Considerations, and Ways Forward - Öhlund, Linnea; Wiberg, Mikael (Interacting with computers, 2025)
Abstract The expanding interest in justice-oriented HCI focusing on critical perspectives, structural oppression, and marginalization—often referred to as social justice—is reflected in a growing number of publications over the past few years. Through the continuous growth of social justice in HCI, we argue that now is a good time to provide an overview of the ongoing and current streams of social justice research. We introduce social justice as it has grown in HCI during the last 15 years followed by the most commonly framed theoretical tenets. Secondly, we construct a corpus of 60 HCI articles building on social justice as the main concept. Through our corpus we summarize and present 4 currently ongoing streams of research to further a cohesive, yet fluid understanding of how social justice is shaped and understood within HCI. Describing these interconnected streams also gives us the possibility to frame and describe the current development and move forward as a research community. Based on our study and discussions, we suggest 6 considerations for HCI researchers seeking to work with social justice as a concept, and we emphasize the need for long-term engagement in justice-oriented research to foreground and enable societal change and social good. Through this study, we contribute to the ongoing growth of social justice research in HCI by providing an overview of current streams and ways forward.